2020
DOI: 10.1155/2020/8627824
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network to Estimate the Paddy Yield Prediction Using Climatic Data

Abstract: Paddy harvest is extremely vulnerable to climate change and climate variations. It is a well-known fact that climate change has been accelerated over the past decades due to various human induced activities. In addition, demand for the food is increasing day-by-day due to the rapid growth of population. Therefore, understanding the relationships between climatic factors and paddy production has become crucial for the sustainability of the agriculture sector. However, these relationships are usually complex non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 43 publications
1
42
0
1
Order By: Relevance
“…ough paddy yield prediction models were developed by applying numerous techniques [35,36], this is the first research study on developing a crop-weather model for the paddy yield in Sri Lanka. is research can be extended for the prediction of paddy yield for future seasons or years if the independent variables are available as projected climatic variables.…”
Section: Discussionmentioning
confidence: 99%
“…ough paddy yield prediction models were developed by applying numerous techniques [35,36], this is the first research study on developing a crop-weather model for the paddy yield in Sri Lanka. is research can be extended for the prediction of paddy yield for future seasons or years if the independent variables are available as projected climatic variables.…”
Section: Discussionmentioning
confidence: 99%
“…is model was validated with an accuracy of 97.5%, a sensitivity of 96.3%, and specificity of 98.1% by developing a multilayer perceptron neural network. A similar research work performed on the data of several paddy grown areas in Sri Lanka proved that ANN model (with MSE < 0.386) can be used with less computational time to predict the future paddy yield based on future climatic data [14]. An advanced application of ANN integrated with multiple linear regression (MLR) and penalized regression models for prediction of rice yield based on weather parameters at the west coast of India was presented by Das et al [15].…”
Section: Introductionmentioning
confidence: 90%
“…The research found that all analyzed models produced high-accuracy predictions (the MSE value ranged from 0.01 to 0.39 t•ha −1 ). However, the Levenberg-Marquardt and scaled conjugated gradient algorithms required fewer epochs and a shorter computation time [115]. Gonzalez-Sanchez et al [18], apart from the sum of precipitation, minimum and maximum temperature, relative humidity, and field location, also used solar radiation (in MJ/m 2 ) as an explanatory variable in the prediction of agricultural crops grown in Sinaloa (Western Mexico).…”
Section: Primary Factorsmentioning
confidence: 99%